Strategi pengelolaan hutan mangrove Kampung Kayu Ara Permai Kecamatan Sungai Apit Kabupaten Siak - Johanes Hutagaol; Zulfan Saam; Yusni Ikhwan Siregar (Jurnal Zona, 2021)
Mangrove forest management is an effort to protect mangrove forests into conservation forest areas. This study aims to (1) analyze internal and external factors that influence mangrove forest management and (2) mangrove forest management strategies in Kayu Ara Permai Village, Sungai Apit District, Siak Regency. The research was conducted using qualitative research with descriptive research methods. The data collected consisted of primary and secondary data and were analyzed using the SWOT analysis approach (Strength, Weakness, Opportunity, and Threat). The results of the study showed a strategy in mangrove forest management in Kampung Kayu Ara Permai, namely encouraging community participation in mangrove forest management, capacity building Human resources both for the community and the Laskar Mandiri Conservation group. Development of mangrove ecotourism in Kampung Kayu Ara Permai Encouraging mangrove forest management to become Social Forestry with the Community Forestry scheme